Synthesis of Secondary Amides from N‐Substituted Amidines by Tandem Oxidative Rearrangement and Isocyanate Elimination. Issue 1 (4th December 2014) - Debnath, Pradip; Baeten, Mattijs; Lefèvre, Nicolas; Daele, Stijn Van; Maes, Bert U. W.
Abstract In this work an efficient tandem process transforming N‐substituted amidines into secondary amides has been described. The process involves N‐acylurea formation by reaction of the substrate with bis(acyloxy)(phenyl)‐λ3‐iodane followed by isocyanate elimination. The periodinane reagents are obtained from the commercially available phenyliodine(III) diacetate [PhI(OAc)2, (PIDA)] by ligand exchange with carboxylic acids. The N‐substituted amidine substrates are easily synthesized from readily available nitriles. The method is applicable for secondary amide synthesis, based on both aliphatic and (hetero)aromatic amines, including challenging amides consisting of sterically hindered acids and amines. Moreover, the protocol allows one to combine steric bulk with electron deficiency in the target amides (aniline based). Such compounds are difficult to synthesize efficiently based on classical condensation reactions involving carboxylic acids and amines. Overall, the synthetic protocol transforms a nitrile into a secondary amide in both aliphatic and (hetero)aromatic systems. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>